Evaluation of Chinese Transport Infrastructure Investment Performance in Countries along the Belt and Road Initiative. (9th August 2021) - Yang, Yanbin; Liu, Wei; Li, Kaiyuan; Jin, Yuping; Liang, Shijia
Abstract : Since the launch of the Belt and Road Initiative (BRI) in 2013, Chinese enterprises have invested heavily in transport infrastructure projects. In order to better promote Chinese overseas transport infrastructure investment (TII) and avoid additional risks, it is necessary to scientifically assess the performance of Chinese TII in countries along the BRI and explore the promotion path of Chinese TII performance. For this reason, we used a superefficient slacks-based measurement (SE-SBM) model to calculate Chinese TII performance based on 5 dimensions, including political environment, economic environment, institutional environment, humanistic environment, and social environment. These 5 dimensions were divided into 14 indicators, and we used quantification with indirect data to quantify all indicators. Then, according to the performance value of selected countries, we classified them into high-, medium-, and low-performance areas. Next, combined with the scale of returns and the shadow price of input indicators, we provided the promotion measures of each performance area. Our analysis generates valuable measures to reduce TII risks and better promote the connectivity of countries along the BRI.